2008
DOI: 10.1182/blood-2008-05-156380
|View full text |Cite
|
Sign up to set email alerts
|

p53-mediated apoptosis of CLL cells: evidence for a transcription-independent mechanism

Abstract: The p53 protein plays a key role in securing the apoptotic response of chronic lymphocytic leukemia (CLL) cells to genotoxic agents. Transcriptional induction of proapoptotic proteins including Puma are thought to mediate p53-dependent apoptosis. In contrast, recent studies have identified a novel nontranscriptional mechanism, involving direct binding of p53 to antiapoptotic proteins including Bcl-2 at the mitochondrial surface. Here we show that the major fraction of p53 induced in CLL cells by chlorambucil, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
3
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 52 publications
(88 reference statements)
7
73
3
2
Order By: Relevance
“…Our data are concordant with other studies of haematologic malignancies that showed that nutlin-3a can induce direct translocation of p53 protein to mitochondria resulting in apoptosis. 16,43 However, our results are in contrast with a recent study on chronic lymphocytic leukaemia, in which PFT-a augmented nutlin-3a-induced apoptosis, thus implying that p53-transcriptional and p53-nontranscriptional apoptotic mechanisms can operate antagonistically. 43 In our in vitro system, these two mechanisms seemed to operate in concert, as both PFT-a and PFT-m inhibited nutlin-3a-mediated apoptosis in ALK þ ALCL cells.…”
Section: Discussioncontrasting
confidence: 56%
“…Our data are concordant with other studies of haematologic malignancies that showed that nutlin-3a can induce direct translocation of p53 protein to mitochondria resulting in apoptosis. 16,43 However, our results are in contrast with a recent study on chronic lymphocytic leukaemia, in which PFT-a augmented nutlin-3a-induced apoptosis, thus implying that p53-transcriptional and p53-nontranscriptional apoptotic mechanisms can operate antagonistically. 43 In our in vitro system, these two mechanisms seemed to operate in concert, as both PFT-a and PFT-m inhibited nutlin-3a-mediated apoptosis in ALK þ ALCL cells.…”
Section: Discussioncontrasting
confidence: 56%
“…35 The Burkitt's lymphoma cell lines Ramos and Raji were obtained from ECACC. Cells were maintained in RPMI1640 supplemented with 10% FCS, 2mM glutamine, penicillin/streptomycin and 1mM sodium pyruvate (Life Technologies, UK).…”
Section: Cell Culturementioning
confidence: 99%
“…3-6 A20, also known as TNF a-induced protein 3 (TNFAIP3), is a well-known negative regulator of the NF-kB activation pathway and can attenuate the NF-kB activity triggered by signaling from TNF and Toll-like receptors. 7 In view of these findings, A20 could potentially act as a tumor suppressor gene. Nonetheless, it remains to be investigated whether A20, like other tumor suppressor genes, is also targeted for inactivation by promoter methylation and whether A20 abnormalities impact on clinical presentation and treatment response.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Our current findings are interesting also in light of previous data showing that XAF-1 is a natural antagonist of the inhibitor of apoptosis family proteins, 2 which are believed to contribute to cancer progression and to decrease the sensitivity to drug and radiation therapy. In a recent study, Steele et al 7 showed that the transcriptional blockade of p53 through pifithrin-a (PFTa) increases the Nutlin-3 ability to induce apoptosis facilitating the translocation of p53 to mitochondria. Thus, future studies should be aimed at evaluating whether permissive levels of XAF-1 are necessary for an optimal p53-mediated cytotoxic activity at the mitochondrial level.…”
mentioning
confidence: 99%